2019
DOI: 10.1148/ryai.2019180011
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning–based CT Image Reconstruction: Initial Evaluation Targeting Hypovascular Hepatic Metastases

Abstract: To evaluate the effect of a deep learning-based reconstruction (DLR) method on the conspicuity of hypovascular hepatic metastases on abdominal CT images. Materials and Methods:This retrospective study with institutional review board approval included 58 patients with hypovascular hepatic metastases. A radiologist recorded the standard deviation of attenuation in the paraspinal muscle as the image noise and the contrast-to-noise ratio (CNR). CNR was calculated as region of interest ([ROI] L − ROI T )/N, where R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Another study in 2019 by Nakamura et al evaluated the detectability of hypovascular hepatic metastasis in images reconstructed with AiCE in addition to measuring noise and CNR. They demonstrated less image noise and superior conspicuity for DLR compared to the iterative algorithm [35]. A phantom study by Higaki et al from 2020 additionally examined spatial resolution with a task-based modulation transfer function at 10 % [36].…”
Section: Deep Learning Reconstruction Algorithms In the Clinical Routinementioning
confidence: 99%
“…Another study in 2019 by Nakamura et al evaluated the detectability of hypovascular hepatic metastasis in images reconstructed with AiCE in addition to measuring noise and CNR. They demonstrated less image noise and superior conspicuity for DLR compared to the iterative algorithm [35]. A phantom study by Higaki et al from 2020 additionally examined spatial resolution with a task-based modulation transfer function at 10 % [36].…”
Section: Deep Learning Reconstruction Algorithms In the Clinical Routinementioning
confidence: 99%
“…A few studies on deep learning-based reconstruction have shown that it improved image quality and reduced noise and artifacts better than hybrid IR and MBIR [8,16,28]. Nakamura et al reported that deep learning reconstruction could reduce noise and artifacts more than hybrid IR could and that it may improve the detection of low-contrast lesions when evaluating hypovascular hepatic metastases [16]. While their study did not evaluate low-dose CT, the deep learning model is also considered an effective method with the potential to use lower-dose CT techniques such as sparse sampling with clinically acceptable results [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them focused on quantitative measures such as peak signal-to-noise ratio (PSNR) and structural similarity (SSIM). To the best of our knowledge, there are few studies that radiologists visually evaluate abnormal lesions such as metastasis on CT images processed with deep learning [16]. Furthermore, the quantitative measure, such as PSNR and SSIM, and human perceived quality were not always consistent in agreement [17].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, the TrueFidelity DNN was trained with both patient and phantom data whereas it was trained only with patient data for AiCE. CT images obtained with these algorithms using denoising techniques showed suppressed noise with no change of noise texture or distortion of anatomical and pathological structures (19,(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%